2020
DOI: 10.1175/jhm-d-19-0290.1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Diverse Drought Characteristics from Two Meteorological Drought Indices (SPI and SPEI) in China

Abstract: This study elucidates drought characteristics in China during 1980–2015 using two commonly used meteorological drought indices: standardized precipitation index (SPI) and standardized precipitation–evapotranspiration index (SPEI). The results show that SPEI characterizes an overall increase in drought severity, area, and frequency during 1998–2015 compared with those during 1980–97, mainly due to the increasing potential evapotranspiration. By contrast, SPI does not reveal this phenomenon since precipitation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(75 citation statements)
references
References 64 publications
4
70
0
1
Order By: Relevance
“…Many other studies have also reported drought occurrences in the country [36][37][38]. Similar findings have been reported from North Korea [56][57][58], Japan [58], and China [59,60] that neighbor South Korea. There are also studies from other parts of the globe that have reported increased occurrences of droughts using SPI, SPEI, and SDI [61][62][63].…”
Section: Future Droughtsupporting
confidence: 82%
“…Many other studies have also reported drought occurrences in the country [36][37][38]. Similar findings have been reported from North Korea [56][57][58], Japan [58], and China [59,60] that neighbor South Korea. There are also studies from other parts of the globe that have reported increased occurrences of droughts using SPI, SPEI, and SDI [61][62][63].…”
Section: Future Droughtsupporting
confidence: 82%
“…This process couples the water and carbon cycles and controls surface energy partitioning, thus playing a principal role in land surface and atmosphere/climate feedbacks (Bonan et al, 2008;Matheny et al, 2014a). A warming climate is expected to intensify the global hydrological cycle and induce more frequent and severe droughts (Dai, 2013;Li et al, 2020). Rising temperature will likewise cause an increase in atmospheric vapor pressure deficit (Grossiord et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The probability density function (PDF) that has been used for the SPEI is the log-logistic function, as suggested by Mckee et al (1993) and Vicente-Serrano et al (2010), respectively. Since both Yao et al (2018b) and Li et al (2020) used the SPEI to monitor the drought situation in China, the log-logistic PDFs are available for meteorological sites in China.…”
Section: Speimentioning
confidence: 99%
“…The SPEI is based on the SPI but adds a temperature component that allows the SPEI to account for the effect of temperature on the development of drought through basic water balance calculations (Soh et al 2018;Yao et al 2018b). Li et al (2020) elucidated drought characteristics of China during 1980-2015 using two commonly used meteorological drought indices: SPI and SPEI. Given the fact that potential evapotranspiration increases in a warming climate, Li et al (2020) show that SPEI may be more suitable than SPI in monitoring drought under climate change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation